Civil procedure code - Ahmed, Naimuddin; Bangladesh. Code of Civil Procedure, 1908.; Bangladesh Institute of Law and International Affairs (Dhaka : Bangladesh Institute of Law and International Affairs, 2000)
A comprehensive commentary.
Includes index.
Law
Keywords: Civil procedure -- Bangladesh